Effect of chenodeoxycholic acid and the bile acid sequestrant colesevelam on glucagon-like peptide-1 secretion - Hansen, M.; Scheltema, M. J.; Sonne, D. P.; Hansen, J. S.; Sperling, M.; Rehfeld, J. F.; Holst, J. J.; Vilsbøll, T.; Knop, F. K. (Diabetes, obesity & metabolism, 2016)
Aim To evaluate the effects of the primary human bile acid, chenodeoxycholic acid (CDCA), and the bile acid sequestrant (BAS) colesevelam, instilled into the stomach, on plasma levels of glucagon‐like peptide‐1 (GLP‐1), glucose‐dependent insulinotropic polypeptide, glucose, insulin, C‐peptide, glucagon, cholecystokinin and gastrin, as well as on gastric emptying, gallbladder volume, appetite and food intake. Methods On four separate days, nine patients with type 2 diabetes, and 10 matched healthy control subjects received bolus instillations of (i) CDCA, (ii) colesevelam, (iii) CDCA + colesevelam or (iv) placebo. At baseline and for 180 min after instillation, blood was sampled. Results In both the type 2 diabetes group and the healthy control group, CDCA elicited an increase in GLP‐1 levels compared with colesevelam, CDCA + colesevelam and placebo, respectively (p < 0.05). The interventions did not affect plasma glucose, insulin or C‐peptide concentrations in any of the groups. CDCA elicited a small increase in plasma insulin : glucose ratio compared with colesevelam, CDCA + colesevelam and placebo in both groups. Compared with colesevelam, CDCA + colesevelam and placebo, respectively, CDCA increased glucagon and delayed gastric emptying in both groups. Conclusions CDCA increased GLP‐1 and glucagon secretion, and delayed gastric emptying. We speculate that bile acid‐induced activation of TGR5 on L cells increases GLP‐1 secretion, which, in turn, may result in amplification of glucose‐stimulated insulin secretion. Furthermore our data suggest that colesevelam does not have an acute effect on GLP‐1 secretion in humans.